Penyuluhan Pemanfaatan Plastik, Pemilahan Sampah, dan Pengelolaan Sampah pada Ibu Rumah Tangga - Sulistiyorini, Desy (Apik Cahaya Ilmu, 2024)
Inappropriate use of plastic can cause health problems, including the risk of cancer and tissue damage in the human body. Another problem related to plastic is that global plastic waste production has increased dramatically over the past few decades, giving rise to severe environmental and health challenges. This outreach activity aims to increase public awareness about the safe and correct use of plastic and management of household waste that does not endanger health and has no impact on the environment. The community service activity was attended by around 37 housewives in Cisasah Masjid village, Purwasari Village. Dramaga District, Bogor Regency. Participants were given education regarding types of plastic and their safe use for food and household waste management. Participants were also given a questionnaire regarding knowledge and attitudes regarding plastic waste management. The results show that the majority of participants have good knowledge and attitudes regarding plastic waste management